High-level information fusion management and systems design - Blasch, Erik; Bossé, Éloi, 1956-; Lambert, Dale A. (Artech House intelligence and information operations series., 2012)
High-level information fusion is the ability of a fusion system to capture awareness and complex relations, reason over past and future events, utilize direct sensing exploitations and tacit reports, and discern the usefulness and intention of results to meet system-level goals. This authoritative book serves a practical reference for developers, designers, and users of data fusion services that must relate the most recent theory to real-world applications. This unique volume provides alternative methods to represent and model various situations and describes design component implementations o.